Is Prolonged Sitting a Risk Factor in Developing Hemorrhoids and Anal Fissures? - Gamal E.H.A. Shallaly; El Fatih M. Malik; Mohamed Abdelmonem Ali; Maysa H. M. Hamza; Babikir A. B. Ibrahim; Hassan E.H.M. Ahmed; Mohamed M. I. Elhajahmed; Modather M.E. Salih (Sudan Journal of Medical Sciences, 2023)
Abstract Background: Anal fissures and hemorrhoids are common anal conditions. They cause significant morbidity, social embarrassment, and work absenteeism. In addition, they form a significant workload on the healthcare system. Nevertheless, the etiology of these conditions is still contentious. It has been observed that hemorrhoids and anal fissures are associated with prolonged sitting. This study aims to investigate this observation. Methods: This is a case–control study. We compared 81 patients with symptomatic and endoscopically proven hemorrhoids and/or anal fissures with 162 controls with no symptoms or endoscopic evidence of perianal disease. The study was conducted at Khartoum North Teaching Hospital (KNTH) endoscopy unit between January and December 2019.Demographic data, sitting hours per day, and endoscopic findings of patients and controls were recorded in a proforma. The cases and controls were matched for age, sex, and bowel habits. Data were analyzed and compared using the SPSS version 23. Results: The mean sitting hours for cases was 5.99 (SD 3.4) whereas that for controls was 4.0 (SD 3.0) with a highly significant difference (P < 0.001). Sitting for 5 hr or more per day (exposure) was associated with an increased risk of developing hemorrhoids and/or anal fissures [odds ratio 3.68, 95% CI: 2.1–6.47]. Conclusion: The study showed that sitting down for 5 hr or more per day might increase the risk of developing hemorrhoids and/or anal fissures. This finding could help in the prevention and treatment of these diseases and the reduction of recurrences.